2005
DOI: 10.1017/s1477175600001366
|View full text |Cite
|
Sign up to set email alerts
|

Accepting the universe

Abstract: Hugh Mellor examines both the fine-tuning argument and the suggestion that this is but one of many universes within a great ‘multiverse’.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Indeed, Thomas Austin has suggested that the documentary project might be characterised through its concern with retrieving time: "re/calling the past into the present, and preserving something of the past or present for future contemplation" (Austin 2008, 50). Similarly, as I have discussed elsewhere, modern cosmology attempts to hold all time in the present moment by mapping out the evolution of the universe from its origin in the Big Bang through to its end (Mellor 2016). Documentaries about scientists' understanding of time are thus embedded in an inherent metaphoricity in which the documentary form gives expression to the documentary subject.…”
Section: Two Films About Timementioning
confidence: 96%
“…Indeed, Thomas Austin has suggested that the documentary project might be characterised through its concern with retrieving time: "re/calling the past into the present, and preserving something of the past or present for future contemplation" (Austin 2008, 50). Similarly, as I have discussed elsewhere, modern cosmology attempts to hold all time in the present moment by mapping out the evolution of the universe from its origin in the Big Bang through to its end (Mellor 2016). Documentaries about scientists' understanding of time are thus embedded in an inherent metaphoricity in which the documentary form gives expression to the documentary subject.…”
Section: Two Films About Timementioning
confidence: 96%